The Effect of Discipline and Work Motivation on Employee Performance at the Barru Market Mission Supermarket (Case Study on Barru Highway Market Mission Supermarket) in Barru County - Nurul fitrah fitrah; M. Ikhwan Maulana Haeruddin; Burhanuddin Burhanuddin (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study aims to determine the influence of discipline and work motivation on employee performance at the Barru Highway Market Mission Supermarket (Case Study on the Barru Highway Market Mission Supermarket) in Barru Regency. The free variables in this study are discipline and work motivation while the bound variables are employee performance. The population in this study was all employees at the Barru Market Mission, which was 30 employees. The sample determination technique in this study used a saturated sampling technique, where all members of the population were sampled. Data collection was carried out using questionnaires. The data analysis technique used is multiple linear regression analysis using SPSS 25.00 for windows.From the test results of multiple linear regression analysis can be obtained the following formulation: Y = 10.807 + 0.399X1 + 0.509X2. Meanwhile, the coefficient of determination = 0.414 means that the variables of discipline and work motivation have an influence of 41.4% on employee performance. While the rest is influenced by other variables that were not studied in this study. Partial Test results for X1 obtained Thitung > Ttabel (2.243 > 2.052) with a significance of 0.033 then H1 is accepted and H0 is rejected. Partial Test Results for X2 obtained Thitung > Ttabel (2,909 > 2,052) with a significance of 0.007 then H2 is accepted and H0 is rejected From the results of this study, it can be concluded that discipline and work motivation are very important things to pay attention to the leadership of the Barru Regency Pasar Raya Mission Supermarket, the better the discipline and work and what is applied, the better the performance of employees at the Pasar Raya Mission Supermarket.